2020
DOI: 10.3390/cancers12082280
|View full text |Cite
|
Sign up to set email alerts
|

The Development and Treatment of Lymphatic Dysfunction in Cancer Patients and Survivors

Abstract: Breast-cancer-acquired lymphedema is routinely diagnosed from the appearance of irreversible swelling that occurs as a result of lymphatic dysfunction. Yet in head and neck cancer survivors, lymphatic dysfunction may not always result in clinically overt swelling, but instead contribute to debilitating functional outcomes. In this review, we describe how cancer metastasis, lymph node dissection, and radiation therapy alter lymphatic function, as visualized by near-infrared fluorescence lymphatic imaging. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 137 publications
(205 reference statements)
1
19
0
Order By: Relevance
“…At the time of imaging, the status of the infection was improving, but an inflammatory response may have been present as evidenced by impaired lymphatic function. While there was no clinically apparent lymphedema or measurable change in arm volume, visible dermal backflow was observed similarly to our previously reported findings in breast cancer survivors diagnosed with cancer-related lymphedema and in head and neck patients following LN dissection and radiation treatment [ 7 , 8 ]. We hypothesize that the impaired lymphatic pumping in our patient, caused by proinflammatory conditions or lymphatic blockage, results in dermal backflow.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At the time of imaging, the status of the infection was improving, but an inflammatory response may have been present as evidenced by impaired lymphatic function. While there was no clinically apparent lymphedema or measurable change in arm volume, visible dermal backflow was observed similarly to our previously reported findings in breast cancer survivors diagnosed with cancer-related lymphedema and in head and neck patients following LN dissection and radiation treatment [ 7 , 8 ]. We hypothesize that the impaired lymphatic pumping in our patient, caused by proinflammatory conditions or lymphatic blockage, results in dermal backflow.…”
Section: Discussionsupporting
confidence: 89%
“…Clinical examination and ultrasound showed an enlargement of axillary LN consistent with lymphadenitis. Because lymphatic dysfunction is attributed to the cause of AWS after LN dissection, and because we have previously used investigational near-infrared fluorescence lymphatic imaging (NIRF-LI) to evaluate lymphatic (dys)function following LN dissection [ 7 , 8 ], we sought to observe whether the distal lymphatics draining the site of the infection and draining into the axilla were functional. Subsequently at 8 weeks after the needlestick injury, the patient underwent NIRF-LI under a University of Texas Health Science Center at Houston Institutional Review Board–approved protocol (US Food and Drug Administration investigational new drug/investigational device exemption 102 827) with 7 off-label, intradermal injections of 25 μg of indocyanine green (ICG) in .1 cc of saline, administered on the affected left thumb as well as on the dorsal and volar aspect of both wrists [ 9 , 10 ].…”
Section: Case Reportmentioning
confidence: 99%
“…Abnormal LSG findings or near-infrared fluorescence lymphatic imaging without clinical evidence of disease contralateral to a clinically lymphedematous limb is a relatively common finding. Using near-infrared fluorescence lymphatic imaging, Aldrich et al, 7 however, found dermal backflow (an early sign of lymphatic dysfunction) in breast cancer patients before axillary lymph node dissection and similar findings after dissection, which preceded the development of arm swelling. As they suggested, "Investigators hypothesize that cancer treatment serves as a 'second hit' in patients with germline mutations associated with pathways associated with lymphangiogenesis."…”
Section: Paradoxdthe Predestined Development Of Led In Certain Patientsmentioning
confidence: 94%
“…Acquired lymphedema is a complex disease caused by cancer treatment or parasitic infection and few effective treatments are available for lymphedema. 1 , 2 , 3 It is urgently needed to develop new experimental approaches and therapeutic strategies. 3 In this study, we address a new role and mechanism of MSC‐ex (human umbilical cord Wharton's jelly mesenchymal stem cells derived exosome) in lymphedema treatment.…”
Section: Figurementioning
confidence: 99%
“…MSC-ex may ameliorate It is a promising therapeutic strategy to treat lymphedema. Zhao Ting 1,2 Yan Zhi-xin 3 Tan You-wen 4 Yang Fu-ji 1 Sun Hui 1 Mao Fei 1 Zhu Wei 1 Xu Wen-rong 1 Qian Hui 5 Yan Yong-min 5…”
mentioning
confidence: 99%